The Asymmetry of Access to Public Data - Sikora-Fernandez, Dorota; Stawasz, Danuta (Journal of Public Governance, 2023)
Objective: This paper critically investigates the phenomenon of asymmetrical access to public data, a growing issue in our increasingly digitised society. Its objective is identify the root causes of asymmetry in access to public data and to propose solutions that would promote greater transparency and fairness, and foster citizen participation in public life.Research Design & Methods: The research section includes the analysis of the users of the Internet in the context of using government websites or applications by income group, age group, and place of residence. Then, the R-Pearson linear correlation analysis was used to examine the relationship between the mentioned variables.Findings: The study shows the presence of a digital divide within Poland, attributing its existence to several factors including income, educational attainment, residential location, and age. This divide encompasses not merely the accessibility of digital networks but extends to the competence required to effectively utilize these resources. Furthermore, the research highlights a significant correlation between one’s level of education and their proficiency in utilizing digital tools and conducting information searches on the internet.Implications/Recommendations: To reduce asymmetry in access to public data, policymakers should focus on creating open, user-friendly data portals with standard formats and detailed metadata. Engaging in public consultations can tailor accessibility to community needs, while partnerships with educational and non-profit organisations can offer training to enhance data utilisation skills. Such strategies aim to democratise data access, ensuring it serves a broad and diverse audience effectively.Contribution/ Value Added: The research confirms the existence of a digital divide in Poland, and some of the factors are income level, education, place of residence, and age. The gap is not only about access to the network, but also about the ability to use it. In addition, familiarity with digital tools and the ability to search for information online are strongly related to education level. Analysing the accessibility of public data in the context of income, we note that the higher the income, the higher the percentage of people using public administration online. The analysis also shows that older citizens, despite being the group least likely to use the Internet, have seen the greatest increase in regular Internet use over the studied period, in contrast to teenagers and young adults.Article classification: research articleKeywords: public data; data asymmetry; data governanceJEL O38, O36, H4